Comparative analysis of enteroscopy, computed tomography enterography, and intestinal ultrasound for the evaluation of small bowel Crohn’s disease - Bo Peng; Zhongcheng Liu; Zicheng Huang; Huixian Lin; Zhiyue Wang; Qin Guo (Therapeutic Advances in Gastroenterology)
Background: The comparable evaluation of computed tomography enterography (CTE), enteroscopy, and intestinal ultrasound in small bowel Crohn’s disease (CD) is imprecise. Objectives: The purpose of this study was to analyze the findings of enteroscopy, CTE, and intestinal ultrasound to determine the advantages and disadvantages of each method for the evaluation of small bowel CD. Design: It was a single-center, observational, retrospective study. Methods: The differences in localization of disease lesions, mucosal inflammation, and transmural inflammation between enteroscopy, CTE, and intestinal ultrasound for evaluation of small bowel CD were compared. Results: A total of 198 patients with small bowel CD were included in the analysis. CTE and intestinal ultrasound had a lower detection rate of upper intestinal lesions compared with enteroscopy ( p  < 0.05). Enteroscopy was better than CTE and intestinal ultrasound in the detection of stenosis ( p  < 0.001), and the assessment of fistula by CTE was better than that by enteroscopy and intestinal ultrasound ( p  < 0.05). Enteroscopy, CTE, and intestinal ultrasound differed in the assessment of inflammatory activity, and the agreement of the three methods was poor (all intra-class correlation coefficient <0.75). Conclusion: Enteroscopy is superior to CTE and intestinal ultrasound for the assessment of upper intestinal CD lesions. Enteroscopy, CTE, and intestinal ultrasound were not consistent in evaluating inflammatory activity, and the three methods may need to be combined for an accurate assessment.